Natural pectin-based edible composite coatings with antifungal properties to control postharvest decay and reduce losses of ‘valencia’ oranges - Álvarez, María Victoria; Taberner, Verònica; Fernández-Catalán, Asunción; Martínez-Blay, Victoria; Argente-Sanchis, Maricruz; Palou, Lluís; Pérez-Gago, María B. (2022)
The potential of essential oils (EOs) and natural plant extracts to inhibit Penicillium digitatum (PD), Penicillium italicum (PI), and Geotrichum citri-aurantii (GC), the most economically important pathogens causing postharvest diseases of citrus fruits, was evaluated in in vitro studies.